“We also like to be surprised”: Disruption, provocation and surprise in the music of Christian Wolff - Thomas, Philip; Payne, Emily (Circuit, 2020)
This article explores the ways in which the music of experimental composer Christian Wolff engenders surprise through processes of disruption and provocation. The contexts under examination are: scores which employ cueing strategies; improvisatory pieces; ensemble pieces; pieces for solo piano; and Wolff’s practice as an improvising musician. These case studies show how Wolff’s music occupies a particular position between improvisation and composition. In examining the space that Wolff’s music opens up for contingency and play, and in adopting a view of indeterminacy as understood through performance rather than limited by its notation, the article puts forward a view of indeterminacy grounded in sociality. More broadly, in its contribution to the body of literature investigating the role of notation in improvisation practices, the article invites a reconsideration of the ontological understandings of composition, improvisation, and performance.